Penggunaan Konjungsi Koordinatif ‘Dan’ dalam Novel Sesuk Karya Tere Liye: Pendekatan Linguistik Korpus - Tulaini, Puji Rahma; Juita, Novia (Persona: Kajian Bahasa dan Sastra, 2024)
This research is motivated by linguistic phenomena contained in a novel or literary work. This research aims to describe the use of the coordinating conjunction 'and' in the novel Sesuk by Tere Liye. This research uses a qualitative descriptive method. The data for this research are sentences containing the coordinating conjunction 'and'. The source of research data is the novel Sesuk by Tere Liye. The data collection technique uses documentation techniques with corpus linguistic methods through the KORTARA application. The data collected in this research was obtained through the Kortara application. The data collected in this research is then analyzed using the following steps: (1) downloading the data obtained from the target corpus in the Kortara application into an Excel file, (2) identifying the data according to the research objectives, (3) classifying the data that has been identified according to with research objectives, (4) formulating research findings, (5) draw conclusions. From the research findings, it can be concluded that the use of the coordinating conjunction 'and' in the novel Sesuk Tere Liye is based on its position, namely the first coordinating conjunction which is located between words is 343 data with a percentage of 61.14%. Second, there are 65 coordinating conjunctions located between phrases with a percentage of 11.58%. Third, there are 67 coordinating conjunctions located between clauses with a percentage of 11.94%. And fourth, there are 86 coordinating conjunctions located between sentences with a percentage of 15.32%.